THE INFLUENCE OF APPLICATION OF LECTURE METHOD ON LEARNING OUTCOMES OF STUDENT FINANCIAL LITERACY - Girang Permata Gusti (Jurnal Pengabdian Sriwijaya, 2019)
The importance of financial literacy knowledge for elementary school children is needed, but the right method is needed to teach it. This experimental research seeks to measure empirically the extent of the effectiveness of the lecture method on the ability of students to understand each material being taught. The stages of the study were conducted using the pre-test and post-test methods and by using the same participants as many as 31 elementary school students. The results showed that there was a significant influence on the ability of students to understand each lesson delivered (after receiving treatment)